CREATING EMPLOYEE WORKING SKILLS AND PERFORMANCE THROUGH ORGANIZATIONAL TRAINING PRACTICES IN ABC TIRE MANUFACTURING COMPANY - Iamsomboon, Nuttakit; Sukortprommee, Sarakul; Klinpratum, Varisara (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2020)
This research aimed at studying the effects of organizational training practices on creating employee working skills and employee performance in ABC Tire Manufacturing Company, which it is located in Pathum Thani Province. The samples were of 400 employees working in ABC Tire Manufacturing Company in Pathum Thani Province. The questionnaires were used to collect the data with the purposive sampling and convenient sampling methods. Data analysis consisted of descriptive statistics including frequency, percentage, mean and standard deviation and inferential statistics including structural equation model (SEM). The results showed that most of the respondents were male (366 persons or 91.5%), aged between 21-30 years old (120 persons or 30.0%) and between 41 – 50 years old (120 person or 30%), graduated lower than bachelor’s degree (288 persons or 72.0%), worked as operational staff (330 persons or 82.5%), worked for 6 – 10 years (138 persons or 34.5%), and earned between 25,001 - 35,000 baht (138 persons or 34.5%), respectively. The employees had opinion related organizational training practices, working skills and performance in high level. The SEM revealed that organizational training had a direct effect on working skills, managing skills, and leading skills and an indirect effect on employees’ performance with standardized coefficient as of